The learning styles of first year distance education students - Hutton, J. Lynley (Working papers (Open Polytechnic of New Zealand), 1998)
"... report on the results of research in progress on learning styles of first year students studying with The Open Polytechnic of New Zealand ... and discusses the instructional design implications ..."--P. iii.